A Survey on E-hailing and Demand Responsive Transit (DRT) services as First Last Mile Mode in Putrajaya - Chin, Kar Keong; Gan, Jia Jiun; Yuen, Choon Wah; Pavin a/l Ravi,; Soo, En Tong; Chu, May Yen (Recent Trends in Civil Engineering and Built Environment, 2025)
Demand-responsive transport (DRT) services, which include shared ride sourcing and microtransit, provide a flexible travel option that could complement traditional fixed transit (FT) systems. By combining on-demand and fixed-route services, there is potential for enhanced mobility and expanded service coverage. However, it is still unclear whether DRT services actually achieve these expected benefits. As of March 7, 2023, the Land Public Transport Agency (APAD) of Malaysia's Ministry of Transport has registered 16 e-hailing companies operating in the country. There are currently about 70,000 vehicles providing e-hailing services in the Klang Valley area. In Malaysia, an e-hailing vehicle is defined as a motor vehicle with 4 to 11 seats (including the driver) used to transport passengers for a fare. Fares may be paid by individual passengers or collectively for shared rides along the same route, and each ride must be pre-booked through a mobile app operated by a registered company. Since the introduction of the MyTeksi App in 2012 (which rebranded as Grab in 2016), e-hailing services have become a key part of the public transport system in the Klang Valley. These services have improved accessibility to Rail Transit stations, serving as a First-Last Mile solution. However, urban transport planners are concerned that e-hailing services may not effectively reduce the number of motor vehicles on the roads, which continues to contribute to severe traffic congestion during peak hours. Ensuring effective first-last mile transportation is crucial for developing a sustainable transport system. However, many residents struggle with issues such as connectivity, morning rush hour congestion, and limited transport options. In this study, we analyzed the transportation modes of residents in Putrajaya, using data collected from on-site surveys. We investigated both individual-level and contextual factors affecting first-last mile travel behavior. Our findings indicate that 46% of Putrajaya residents are using e-hailing and DRT services currently. Results also shows that the top two highest trip purposes, working trip and leisure trip has different peak demand hours. Most of the Putrajaya residents use e-hailing and DRT for first-last mile trips. More than half of the private vehicles users in Putrajaya are willing to use e-hailing and DRT if the current service are improved.